Discharge and Optical Emission Spectrum Characteristics of a Coaxial Dielectric Barrier Discharge Plasma-Assisted Combustion Actuator. (24th June 2020) - Liu, Pengfei; He, Liming; Zhao, Bingbing
Abstract : A coaxial dielectric barrier discharge plasma-assisted combustion actuator (DBD-PACA) system was set up to study its discharge and optical emission spectrum (OES) characteristics in space in this paper. Results showed that each discharge cycle can be divided into four stages: a, b, c, and d. Discharge-on only occurred in stages b and d. Comparatively, the discharge intensity was larger in stage d due to the memory effect of excited electrons. Moreover, Lissajous figure and current-voltage methods were utilized to calculate the power of the coaxial DBD-PACA, and both methods produced roughly similar results. The power presented an upward trend with increasing input voltage and airflow rate. In addition, numerous second positive system (SPS) excited nitrogen molecules were detected from the OES signals. The intensity of the spectral lines (297.54 nm, 315.76 nm, 336.96 nm, and 357.56 nm) first increased, then maintained, and then increased rapidly with the increased radius; however, the intensity of the spectral lines (380.34 nm, 405.80 nm, and 434.30 nm) basically remained unchanged, then increased, and finally decreased with the increased radius. The vibrational temperature first decreased quickly and then increased and reached the minimum at r  = 18 mm with the increased radius. The vibrational temperatures at all collection points decreased with the increased input voltage. However, within the range of 0–280 L/min, when r was lower than 15 mm, the vibrational temperatures first increased rapidly and then decreased slowly; when r was greater than 15 mm, the vibrational temperatures first increased and then basically remained stable.